IMPLEMENTASI ALGORITMA VIGENERE CIPHER UNTUK ENKRIPSI DAN DEKRIPSI PADA PERESEPAN DATA OBAT DI PUSKESMAS MERTOYUDAN 1 KABUPATEN MAGELANG - Dwi Astuti; Cisilia Sundari (Politeknik Bisnis Indonesia, 2022)
Puskesmas is a place to provide health and medical services for the community. Every patient who seeks treatment at a doctor at the health center always gets a message containing a prescription for the drug. The problem that often occurs is the large number of drug prescribing processes that occur without being based on a system, can cause errors in drug prescribing and can be fatal for patients. The purpose of this research is to make an electronic encrypted prescription application using the Vigener Cipher method. The implementation of this system uses the Vigener Cipher Algorithm in securing prescription drug data. The Vigener Cipher algorithm can perform encryption and decryption processes. System Design with Context Diagram. The result of this study is that the application of drug prescribing data using the Vigener Cipher Algorithm has been able to secure drug prescribing properly. In the PARASETAMOL Drug Data Test, key: CXWDFHHJYVW, result: RXNDXLAJKJH. Functional Testing Results obtained results that are accepted in all test scenarios and Validity Test Results obtained 100% valid results.